The shephard boy and the wolf - Robbins; Rita (Jamaica Mind to Mind, 2016)
Once, a shepherd boy took care of the sheep for the village. One day, he felt bored so he decided to have some fun. He cried out, (3y (BWolf! Wolf!(3y (BThis book is printed in large print and beautiful page design. Read till the last page and learn the moral values behind this story.s